1980
DOI: 10.1152/ajpheart.1980.238.2.h176
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective actions of prostacyclin during hypoxia in the isolated perfused cat liver

Abstract: The cytoprotective effect of prostacyclin (PGI2) was examined using hypoxic cat livers perfused with Krebs-Henseleit buffer at constant flow. PGI2 infusion (10 ng . g-1 . min-1) showed no direct vasodilator effect on the hepatic circulation under conditions of normoxia or hypoxia, as studied by changes in perfusion pressure. Hypoxia induced a marked decline in hepatic oxygen consumption, an increase in perfusion pressure, and in perfusate cathepsin D and LDH activity in the hepatic effluent indicating lysosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 0 publications
0
53
0
1
Order By: Relevance
“…Serum levels of The protective effect of PGE 2 and PGE 1 on acute liver injury is well known. [13][14][15][16][17][18][19][20][21][22] Because biological activity of PGE 2 is almost identical to PGE 1 , 41 and PGE 2 is the main prostanoid secreted by cultured Kupffer cells, 42 we examined hepatic PGE 2 content. Cytoprotective action of PGE 2 was exerted in several kinds of liver injuries such as D-GalN, 13,19,22 carbon tetrachloride, 14,16,20 a-naphtylisothiocyanate, 15 lipopolysaccharide, 18 and immune reaction against liver antigen.…”
Section: Effect Of Anti-pge 2 Antibody On D-galn -Induced Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of The protective effect of PGE 2 and PGE 1 on acute liver injury is well known. [13][14][15][16][17][18][19][20][21][22] Because biological activity of PGE 2 is almost identical to PGE 1 , 41 and PGE 2 is the main prostanoid secreted by cultured Kupffer cells, 42 we examined hepatic PGE 2 content. Cytoprotective action of PGE 2 was exerted in several kinds of liver injuries such as D-GalN, 13,19,22 carbon tetrachloride, 14,16,20 a-naphtylisothiocyanate, 15 lipopolysaccharide, 18 and immune reaction against liver antigen.…”
Section: Effect Of Anti-pge 2 Antibody On D-galn -Induced Livermentioning
confidence: 99%
“…The percentage of PCNA-positive cells tocellular necrosis caused by several hepatotoxins. [13][14][15][16][17][18][19][20][21][22] It has also been reported that HGF stimulated prostaglandin E 2 in WT mice was very low at 0 hours and 24 hours after treatment, but increased at 48 hours. To clarify the mecha-(PGE 2 ) production through increases in both cytosolic phospholipase A 2 and cyclooxyganase activity in human gastric nisms via which HGF acts, we measured hepatic HGF and prostaglandin E 2 (PGE 2 ) contents after D-GalN administration carcinoma TMK-1 cells 23 and primary cultured rat hepatocytes.…”
mentioning
confidence: 99%
“…Perhaps this improvement is associated with the so-called 'cytoprotective' activity of prostacyclin, which has been proposed not only in whole animals (Ogletree et al, 1979;Schror et al, 1981), but also in a variety of isolated tissues, in which the effects of prostacyclin must be due to factors other than blood flow (Araki & Lefer, 1980;Robert, 1984;Smith et al, 1984b).…”
Section: Microsphere Studiesmentioning
confidence: 99%
“…In addition to these effects on platelet and vascular smooth muscle, PGI2 has been shown to possess a cytoprotective effect, which may be useful for preservation of platelets (Blackwell et al, 1982) and protection of various tissues from ischaemia or hypoxia (Ogletree et al, 1979;Araki & Lefer, 1980). Therefore, the present study was conducted to investigate whether or not beraprost has a cytoprotective effect in a canine model of transient global cerebral ischaemia.…”
Section: Introductionmentioning
confidence: 99%